PENGEMBANGAN E-MODUL INTERAKTIF SEBAGAI SUMBER BELAJAR MATA PELAJARAN INFORMATIKA KELAS X TKJ DI SMK TAMAN SISWA PADANG - Latifah, Fahmi; Alfiriani, Adlia; Darman, Regina Ade (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The problem in this research is that there are still many teachers who use printed teaching materials, printed modules make the learning process less interesting, less interactive, informatics learning tends to use presentation methods which makes students bored. This research aims to produce interactive e-modules as a valid and practical learning resource for informatics subjects. This research applies the Research and Development (RD) method with the ADDIE development model. To collect data in this research, an instrument in the form of a questionnaire was used, a Likert scale was used as an assessment instrument. The research subjects consisted of three lecturers from the PGRI University of West Sumatra, one teacher from SMK Taman Siswa Padang, as well as all class X students of the Computer and Network Engineering Skills Program (TKJ) SMK Taman Siswa Padang. The research results show that the assessment validation test by media experts produced an average score of 84% which is classified as very valid. Meanwhile, the evaluation carried out by material experts produced an average score of 91%, also included in the very valid category. The practicality test carried out by the teacher reached 93% in the very practical category, while the practicality from the student's perspective reached 82% in the very practical category. Conclusions based on the data obtained. Interactive e-modules as a learning resource for informatics subjects are feasible and practical to use. This class X informatics e-module can provide convenience for teachers and students because it can be accessed easily and practically via computers, laptops and Android devices. making it easier to use in various locations.